The Effects of the Affordable Care Act on Health Care Access and Utilization Among Asian American Subgroups. Issue 11 (November 2019) - Park, Sungchul; Stimpson, Jim P.; Pintor, Jessie K.; Roby, Dylan H.; McKenna, Ryan M.; Chen, Jie; Ortega, Alexander N.
Abstract : Objectives: We examined changes in health care access and utilization associated with the Patient Protection and Affordable Care Act (ACA) for different Asian American subgroups relative to non-Latino whites (whites). Research Design: Using 2003–2017 California Health Interview Survey data, we examined changes in 4 health care access measures and 2 utilization measures among whites and 7 Asian American subgroups. We estimated the unadjusted and adjusted percentage point changes on the absolute scale from the pre-ACA to post-ACA periods. Adjusted estimates were obtained from multivariable logistic regression models that controlled for predisposing, enabling, and need factors. We also estimated the pre-ACA to post-ACA changes between whites and Asian American subgroups using a difference-in-difference approach. Results: After the ACA was implemented, uninsurance decreased among all Asian American subgroups, but improvements in disparities relative to whites in these measures were limited. In particular, Koreans had the largest absolute reduction in uninsurance (−16.8 percentage points) and were the only subgroup with a significant reduction in terms of disparities relative to whites (−10.1 percentage points). However, little or no improvement was observed in the other 3 access measures (having a usual source of care, delayed medical care in past year, or delayed prescription drug use in past year) and 2 utilization measures (having a physician visit or emergency department visit in past year). Conclusions: Despite coverage gains among Asian American subgroups, especially Koreans, disparities in access and utilization persisted across all Asian American subgroups.